THE STUDY OF RELATED FACTOR BETWEEN 13C–UBT HP POSITIVE AND UPPER GASTROINTESTINAL BLEEDING IN PATIENTS WITH ACS DURING HOSPITALISATION. (8th October 2012) - Fu, Mingwei; Wang, Lei
Abstract : Objectives: To investigate related factor between 13 C–UBT Hp positive and upper gastrointestinal bleeding in patients with STEMI and NSTEMI during hospitalisation. Methods: Prospective analysis of 160 patients with STEMI and NSTEMI hospitalised to the CCU from May 2011 to November 2011. To observe the prevalence of 13 C –UBT Hp positive of patients and 50 healthy persons as control group, at the same time, learn the incidence of upper gastrointestinal bleeding, and study the interrelation between bleeding and Hp positive, as well as various risk factors. The Patients all be followed up for 3 months, all MACE (include recurrent angina pectoric, readmitted in hospital for heart failure, upper gastrointestinal bleeding, death for all causes) will be recorded during the 3 months. Results: 90 out of 160 patients are 13 C–UBT Hp positive (56%), whereas, the incidence of Hp infection in control group is 42%, the difference is statistically (p=0.04). There are no interrelation between age, sex, smoking, hypertention, diabetes mellitus and Hp infection in ACS patients (p>0.05), the prevalence of Hp infection is not different between STEMI and NSTEMI patients (p>0.05). There is no difference of serum lipid, hs-CRP, FIB between 13 C –UBT Hp positive and Hp negative group.8 of 160 patients suffered from upper gastrointestinal bleeding during hospitalisation (5%), the prevalence of upper gastrointestinal bleeding makes no senses between Hp positive and Hp negative patients. Predictors of upper gastrointestinal bleeding included advanced age (≥70) (p=0.004), taken aspirin for long time (p=0.03), history of peptic ulcer (p=0.04) and bleeding (p=0.01), higher value of serum creatinine (>2 mg/dl, p=0.01), insertion of IABP (p=0.003). Conclusions: 56% of these patients are suffered from Hp infection, significantly higher than that in control group. The prevalence of upper gastrointestinal bleeding in patients with STEMI and NSTEMI are still high (5%), advanced age, history of upper gastrointestinal bleeding and higher value of serum creatinine (>2 mg/dl) significantly increase the incidence of upper gastrointestinal bleeding, Hp infection may no be the predictor of upper gastrointestinal bleeding.